An Alternative Metal-Free Aerobic Oxidative Cross-Dehydrogenative Coupling of Sulfonyl Hydrazides with Secondary Phosphine Oxides - Liu, Teng; Zhang, Yanqiong; Yu, Rong; Liu, Jianjun; Cheng, Feixiang (Synthesis, 2020)
An alternative metal-free, efficient and practical approach for the preparation of phosphinothioates is established via the aerobic oxidative cross-dehydrogenative coupling (CDC) of sulfonyl hydrazides with secondary phosphine oxides catalyzed by tetrabutylammonium iodide (TBAI) in the presence of atmospheric oxygen. The strategy provides an array of diverse phosphinothioates in good to excellent yields. Furthermore, two representative bioactive molecules are synthesized on up to gram scale by utilizing this method.
Keywords: phosphinothioates; metal-free; cross-dehydrogenative coupling; secondary phosphine oxides; sulfonyl hydrazides